2022
DOI: 10.1242/jeb.243208
|View full text |Cite
|
Sign up to set email alerts
|

A heterothermic spectrum in hummingbirds

Abstract: Many endotherms use torpor, saving energy by a controlled reduction of their body temperature and metabolic rate. Some species (e.g., arctic ground squirrels, hummingbirds) enter deep torpor, dropping their body temperatures by 23-37°C, while others can only enter shallow torpor (e.g., pigeons, 3-10°C reductions). However, deep torpor in mammals can increase predation risk (unless animals are in burrows or caves), inhibit immune function, and result in sleep deprivation, so even for species that can enter deep… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 80 publications
0
15
0
Order By: Relevance
“…Recent studies of torpor have revealed that torpor can be either “deep” or “shallow” (Mckechnie & Lovegrove 2002; Schleucher 2004; Ruf & Geiser 2015; Shankar et al . 2022).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent studies of torpor have revealed that torpor can be either “deep” or “shallow” (Mckechnie & Lovegrove 2002; Schleucher 2004; Ruf & Geiser 2015; Shankar et al . 2022).…”
Section: Methodsmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted December 12, 2022. ; https://doi.org/10.1101/2022.12.08.519654 doi: bioRxiv preprint conditions such as changes in ambient temperature (Spence & Tingley 2021), weather (Calder & Booser 1973), migration status (Carpenter & Hixon 1988), nutrition (Hainsworth et al 1977;Powers et al 2003), and season (Hiebert 1991). Moreover, the use of torpor appears to be distributed along a continuum (Schleucher 2004;Ruf & Geiser 2015;Shankar et al 2022), and subtle modifications in the frequency of torpor and bout duration are crucial to birds' ability to save energy (Shankar et al 2020b;Wolf et al 2020). As a consequence, the use of torpor varies across species (Krüger et al 1982;Bech et al 1997;Shankar et al 2020b;Wolf et al 2020), within species (Schleucher 2004;Shankar et al 2019Shankar et al , 2020bSpence & Tingley 2021), and even within individuals (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One possibility is that sleep duration in these experiments was influenced by torpor. Like many small endotherms [ 68–71 ], bats can become heterothermic to alleviate the high energetic demands of maintaining a constant body temperature. This results in the expression of torpor, an energy conserving physiological state in which metabolic rate is decreased and body temperature, ventilation and heart rate are depressed [ 72 , 73 ].…”
Section: A Re-examination Of Bat Sleep Durationmentioning
confidence: 99%
“…Males and females have distinctive reproductive roles and polygynous reproductive systems, where leks are prevalent. Hummingbirds may have reached the upper energetic limits of miniaturization of any group of ying vertebrates, adapting their physiology to conserve heat in cold nights (Shankar et al 2022). Their high metabolic rates force them to secure almost constant access to high-energy food sources, in addition to placing severe constraints on their ability to deal with environmental variation, although this has not been an obstacle for the colonization of high-altitude habitats (Altshuler and Dudley 2002).…”
Section: Introductionmentioning
confidence: 99%